Combined in silico investigation and in vitro characterization of the zearalenone detoxification potential of dye-decolorizing peroxidase from Bacillus subtilis 168. (April 2023) - Guo, Yongpeng; Wang, Yanan; Tang, Yu; Ma, Qiugang; Ji, Cheng; Zhao, Lihong
Abstract: Zearalenone (ZEN), one of the most hazardous mycotoxins commonly present in food, causes severe safety risks to human health. In this work, the ZEN detoxification potential of dye-decolorizing peroxidase BsDyP from Bacillus subtilis 168 was investigated by a combined computational and experimental study. Molecular docking and dynamics simulation suggested that BsDyP could allow the binding of ZEN at the γ-edge of heme and surface exposed redox-active Tyr335 residue. Consistently, the recombinant BsDyP expressed in Escherichia coli was found to be capable of directly oxidizing 83% of ZEN with H2 O2 as an electron acceptor. Moreover, the presence of 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) as a redox mediator of BsDyP could enhance ZEN degradation to more than 98% in the pH range of 5.0–10.0. BsDyP-catalyzed ZEN degradation could be regarded as detoxification as the transformation product displayed much less estrogenicity. Moreover, bi-enzymes system including glucose oxidase (GOD) and BsDyP was applied to degrade ZEN in contaminated corn steep liquor and achieved a 33% degradation percentage. The findings suggested that BsDyP could be developed as a biocatalyst for detoxification of ZEN in contaminated food and feed. Highlights: BsDyP could directly oxidize ZEN with H2 O2 as a co-substrate. The presence of ABTS as a redox mediator enhanced BsDyP-catalyzed ZEN degradation. The GOD and BsDyP cascade reaction degraded 33% ZEN in corn steep liquor. ZEN-11, 12-oxide was identified as the transformation product. BsDyP-catalyzed ZEN degradation mitigated its estrogenicity.